Comprehensive Comparison of Cultivable Norovirus Surrogates in Response to Different Inactivation and Disinfection Treatments - Cromeans, Theresa (American Society for Microbiology, 2014)
Human norovirus is the leading cause of epidemic and sporadic acute gastroenteritis. Since no cell culture method for human norovirus exists, cultivable surrogate viruses (CSV), including feline calicivirus (FCV), murine norovirus (MNV), porcine enteric calicivirus (PEC), and Tulane virus (TuV), have been used to study responses to inactivation and disinfection methods. We compared the levels of reduction in infectivities of CSV and Aichi virus (AiV) after exposure to extreme pHs, 56°C heating, alcohols, chlorine on surfaces, and high hydrostatic pressure (HHP), using the same matrix and identical test parameters for all viruses, as well as the reduction of human norovirus RNA levels under these conditions. At pH 2, FCV was inactivated by 6 log(10) units, whereas MNV, TuV, and AiV were resistant. All CSV were completely inactivated at 56°C within 20 min. MNV was inactivated 5 log(10) units by alcohols, in contrast to 2 and 3 log(10) units for FCV and PEC, respectively. TuV and AiV were relatively insensitive to alcohols. FCV was reduced 5 log(10) units by 1,000 ppm chlorine, in contrast to 1 log(10) unit for the other CSV. All CSV except FCV, when dried on stainless steel surfaces, were insensitive to 200 ppm chlorine. HHP completely inactivated FCV, MNV, and PEC at ≥300 MPa, and TuV at 600 MPa, while AiV was completely resistant to HHP up to 800 MPa. By reverse transcription-quantitative PCR (RT-qPCR), genogroup I (GI) noroviruses were more sensitive than GII noroviruses to alcohols, chlorine, and HHP. Although inactivation profiles were variable for each treatment, TuV and MNV were the most resistant CSV overall and therefore are the best candidates for studying the public health outcomes of norovirus infections.